Desenvolvimento local sustentável através da produção concentrada de madeira em tora no estado do Pará - FILGUEIRAS, Gisalda Carvalho (Universidade Federal do Pará, 2023)
The expansion of the agricultural and cattle-raising frontier, in the State of Pará, increased from the 1960s until the beginning of the year 2000, which resulted in a permanent class struggle, from the economic, social, institutional, but mainly environmental, point of view. In 2012, Pará became the main timber producer in Brazil, according to statistics from the extractive sector and forestry. Given this production, the present work sought to analyze the wood market at world, national and regional level, with emphasis on the concentration of this product in Pará territory. The results indicate the existence of continuous production and, still, concentrated in a few municipalities of Pará, both through the Locational Gini Index and the Normalized Concentration Index. Therefore, shared management among local productive actors and the adoption of sustainable local development practices - forest management - are of the utmost importance for the production of wood products to continue generating employment and income for of Pará.